Estudio de las estrategias de comunicación del Gobierno Nacional de Daniel Noboa en la red social “X” referente a la Consulta Popular desarrollada el 21 de abril de 2024 - Diaz Alulima, Iris Katyusca (2025)
The general objective of this study is to analyze the communication strategies implemented by the National Government of Daniel Noboa in the social network X during the electoral campaign of the Popular Consultation of April 21, 2024. For this, a mixed approach was used, in the quantitative method, observation matrices were developed to study the 47 publications published by the National Government, in the qualitative method, semi-structured interviews were conducted with experts in political communication. The results reflect that the government used communication strategies based on the segmentation of audiences and the elaboration of simplistic and emotional messages, designed to go viral, using priority issues such as security and employment. The messages managed to position themselves in urban sectors and obtained a high level of engagement on the X platform with users, but inconsistencies were evidenced in the alignment with the discourses of the different media, as well as a disconnection with popular and rural communities. It was also reflected that the publications lacked a persuasive narrative, which limits their effectiveness on public opinion. In conclusion, although the X strategy strengthened the government's digital presence, it showed weaknesses in its capacity to generate an emotional link and a convincing narrative. Social network X allowed the National Government to position certain key messages but failed to generate a significant impact on the electorate. The study evidences the need for comprehensive planning that adapts to all audiences